Attention and Visual Motor Integration in Young Children with Uncorrected Hyperopia. Issue 10 (October 2017) - Kulp, Marjean Taylor; Ciner, Elise; Maguire, Maureen; Pistilli, Maxwell; Candy, T. Rowan; Ying, Gui-shuang; Quinn, Graham; Cyert, Lynn; Moore, Bruce
Abstract : SIGNIFICANCE: Among 4- and 5-year-old children, deficits in measures of attention, visual-motor integration (VMI) and visual perception (VP) are associated with moderate, uncorrected hyperopia (3 to 6 diopters [D]) accompanied by reduced near visual function (near visual acuity worse than 20/40 or stereoacuity worse than 240 seconds of arc). PURPOSE: To compare attention, visual motor, and visual perceptual skills in uncorrected hyperopes and emmetropes attending preschool or kindergarten and evaluate their associations with visual function. METHODS: Participants were 4 and 5 years of age with either hyperopia (≥3 to ⩽6 D, astigmatism ⩽1.5 D, anisometropia ⩽1 D) or emmetropia (hyperopia ⩽1 D; astigmatism, anisometropia, and myopia each <1 D), without amblyopia or strabismus. Examiners masked to refractive status administered tests of attention (sustained, receptive, and expressive), VMI, and VP. Binocular visual acuity, stereoacuity, and accommodative accuracy were also assessed at near. Analyses were adjusted for age, sex, race/ethnicity, and parent's/caregiver's education. RESULTS: Two hundred forty-four hyperopes (mean, +3.8 ± [SD] 0.8 D) and 248 emmetropes (+0.5 ± 0.5 D) completed testing. Mean sustained attention score was worse in hyperopes compared with emmetropes (mean difference, −4.1; P < .001 for 3 to 6 D). Mean Receptive Attention score was worse in 4 to 6 D hyperopes compared with emmetropes (by −2.6, P = .01). Hyperopes with reduced near visual acuity (20/40 or worse) had worse scores than emmetropes (−6.4, P < .001 for sustained attention; −3.0, P = .004 for Receptive Attention; −0.7, P = .006 for VMI; −1.3, P = .008 for VP). Hyperopes with stereoacuity of 240 seconds of arc or worse scored significantly worse than emmetropes (−6.7, P < .001 for sustained attention; −3.4, P = .03 for Expressive Attention; −2.2, P = .03 for Receptive Attention; −0.7, P = .01 for VMI; −1.7, P < .001 for VP). Overall, hyperopes with better near visual function generally performed similarly to emmetropes. CONCLUSIONS: Moderately hyperopic children were found to have deficits in measures of attention. Hyperopic children with reduced near visual function also had lower scores on VMI and VP than emmetropic children.